Nursing Care for XDR-TB Complicated by Infected Bronchiectasis and Malnutrition: A Case Report - Sitopu, Robin Ferdiansyah; Halawa, Afeus; Basri, Basri; Aritonang, Murni; Kaban, Fitriyana Br (Jurnal Keperawatan Priority, 2026)
Extensively drug-resistant tuberculosis (XDR-TB) presents a formidable challenge, often exacerbated by irreversible structural lung damage and severe malnutrition. Roy’s Adaptation Model (RAM) was employed as the theoretical framework to address the profound physiological and psychosocial disruptions in a high-complexity case. This report describes the integrated, nurse-led management of a patient with XDR-TB and destroyed lung syndrome during the acute stabilization phase. A 39-year-old woman with a decade-long history of TB treatment failure was admitted to a national referral hospital with XDR-TB, profound cachexia (BMI 13.96 kg/m2), and severe hypercapnia (pCO2 94.7 mmHg). During a 72-hour acute stabilization period, integrated nursing-led interventions including the Active Cycle of Breathing Technique (ACBT), therapeutic positioning, and a high-calorie, high-protein regimen resulted in marked clinical improvement. Respiratory stabilization allowed for oxygen weaning from 5 to 4 L/min with an SpO2 increase to 97%. Breaking the catabolic cycle was evidenced by weight stabilization (maintained at 35 kg) and a positive metabolic shift, alongside significantly improved oral intake (80–90% of requirements).. Functional status progressed from total bed rest to independent short-distance ambulation without desaturation. Comprehensive nursing interventions, focusing on airway clearance and acute metabolic stabilization, play a pivotal role in the rapid stabilization of complex XDR-TB cases. Highlighting outcomes within the first 72 hours demonstrates that structured nursing care acts as a catalyst for physiological adaptation, even in the presence of severe anatomical lung destruction.